Anisotropic Kernels for Coordinate-Based Meta-Analyses of Neuroimaging Studies - Radua, Joaquim; Rubia, Katya; Canales, Erick J.; Pomarol-Clotet, Edith; Fusar-Poli, Paolo; Mataix-Cols, David (Frontiers in Psychiatry, 2014)
Peak-based meta-analyses of neuroimaging studies create, for each study, a brain map of effect size or peak likelihood by convolving a kernel with each reported peak. A kernel is a small matrix applied in order that voxels surrounding the peak have a value similar to, but slightly lower than that of the peak. Current kernels are isotropic, i.e. the value of a voxel close to a peak only depends on the Euclidean distance between the voxel and the peak. However, such perfect spheres of effect size or likelihood around the peak are rather implausible: a voxel that correlates with the peak across individuals is more likely to be part of the cluster of significant activation or difference than voxels uncorrelated with the peak. This paper introduces anisotropic kernels, which assign different values to the different neighboring voxels based on the spatial correlation between them. They are specifically developed for Effect Size Signed Differential Mapping (ES-SDM), though might be easily implemented in other meta-analysis packages such as Activation Likelihood Estimation (ALE). The paper also describes the creation of the required correlation templates for gray matter / BOLD response, white matter, cerebrospinal fluid and fractional anisotropy. Finally, the new method is validated by quantifying the accuracy of the recreation of effect size maps from peak information. This empirical validation showed that the optimal degree of anisotropy and full-width of half-maximum (FWHM) might vary largely depending on the specific data meta-analyzed. However, it also showed that the recreation substantially improved and did not depend on the FWHM when full anisotropy was used. Based on these results, we recommend the use of fully anisotropic kernels in ES-SDM and ALE, unless optimal meta-analysis-specific parameters can be estimated based on the recreation of available statistical maps. The new method and templates are freely available at http://www.sdmproject.com/.